Vehicle navigation in populated areas using predictive control with environmental uncertainty handling - Skrzypczyk, Krzysztof; Mellado, Martin (Archives of Control Sciences, 2017)
Abstract This paper addresses the problem of navigating an autonomous vehicle using environmental dynamics prediction. The usefulness of the Game Against Nature formalism adapted to modelling environmental prediction uncertainty is discussed. The possibility of the control law synthesis on the basis of strategies against Nature is presented. The properties and effectiveness of the approach presented are verified by simulations carried out in MATLAB.